2011
DOI: 10.1167/iovs.11-8112
|View full text |Cite
|
Sign up to set email alerts
|

174delG Mutation in Mouse MFRP Causes Photoreceptor Degeneration and RPE Atrophy

Abstract: The authors have identified a novel null mutation in mouse Mfrp. This mutation causes photoreceptor degeneration and eventual RPE atrophy, which may be related to alterations in the number of RPE microvilli. These mice will be useful to identify a function of MFRP and to study the pathogenesis of atrophic macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(87 citation statements)
references
References 25 publications
9
75
0
Order By: Relevance
“…3F). The MFRP immunoreactive band migrated at about 120 kDa, a much larger size than the predicted molecular mass of 65 kDa of wild-type protein, but consistent with results of previous studies (Won et al, 2008;Fogerty and Besharse, 2011). This high molecular weight band suggests that MFRP may exist as a dimer in RPE cells.…”
Section: Retinal Function and Morphology In Aav Vector-treated Rd6 Micesupporting
confidence: 89%
See 2 more Smart Citations
“…3F). The MFRP immunoreactive band migrated at about 120 kDa, a much larger size than the predicted molecular mass of 65 kDa of wild-type protein, but consistent with results of previous studies (Won et al, 2008;Fogerty and Besharse, 2011). This high molecular weight band suggests that MFRP may exist as a dimer in RPE cells.…”
Section: Retinal Function and Morphology In Aav Vector-treated Rd6 Micesupporting
confidence: 89%
“…C1q is a key component of the classical pathway of complement activation, and is known to be involved in many critical processes including innate and adaptive immunity, inflammation, apoptosis, cell adhesion, and monocyte chemotaxis (Kishore et al, 2004;Lu et al, 2008). Interestingly, a study describing a murine Mfrp null mutant has shown that CTRP5 is upregulated in both rd6 and Mfrp 174delG (Fogerty and Besharse, 2011). Thus, the lack of MFRP protein might lead to uncontrolled signaling by CTRP5, triggering the migration of phagocytic cells from the choroid into the subretinal space, as seen in rd6 mice.…”
Section: Gene Therapy In the Rd6 Mouse Model Of Mfrp Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…A similar phenotype has been described in homozygous Mfrp rdx mice (Fogerty and Besharse, 2011). In humans, MFRP mutations are associated with RP in an ocular syndrome that also includes posterior microphthalmos, foveoschisis and optic nerve head drusen (Ayala-Ramírez et al, 2006; Crespí et al, 2008; Mukhopadhyay et al, 2010; Neri et al, 2012; Zenteno et al, 2009).…”
Section: Introductionsupporting
confidence: 78%
“…Compared to wild-type control iPS-RPE cells, patient iPS-RPE containing a mutation in the Mfrp gene exhibited the loss of apical microvilli as observed by electron microscopy. This result was in stark contrast to the phenotype Mfrp rd6 /Mfrp rd6 mice RPE, which showed higher densities of apical microvilli (Fogerty and Besharse 2011). Because differences in phenotypic expression can be observed among species with the same genetic mutation, it is important to study patient-specific cell lines as a complement to mouse models.…”
Section: Progress Of Retinal Disease Modelingmentioning
confidence: 83%